Clinical Assessment of a New Caries Activity Test Using Dental Plaque Acidogenicity in Children under Three Years of Age - Lee, Hyo-Seol; Lee, Eun-Song; Kang, Si-Mook; Lee, Jae-Ho; Choi, Hyung-Jun; Kim, Baek-Il (The Journal of clinical pediatric dentistry, 2016)
Objectives: The aim of this study was to assess the validity of a new caries activity test that uses dental plaque acidogenicity in children with deciduous dentition. Study design: Ninety-two children under the age of three years old underwent clinical examination using the dft index and examinations with two caries activity tests. Plaque samples for the new Cariview® test and the saliva sample for the conventional Dentocult SM® test were collected, incubated, and scored according to each manufacturers' instruction. The data were analysed using ANOVA and Spearman correlation analyses to evaluate the relationships between the test results and the caries experience. Results: The mean dft index of all of the subjects was 4.73, and 17.4% of the subjects were caries-free. The levels of caries risk based on the new Cariview test score significantly increased with the caries experience (p < 0.01). The test results revealed a stronger correlation with caries indices (dft and dt index) than the conventional SM colony counting method (r = 0.43, r = 0.39, p < 0.01). Conclusions: The new caries activity test to analyse the acidogenic potential of whole microorganisms from dental plaques can be used to evaluate caries risk in children with deciduous teeth.